STRATEGIES FOR SUCCESSFUL ENTRY OF BANDUNG CREATIVE SMES IN FOREIGN MARKET (CASE STUDY: LITTLE BANDUNG IN KOREA) - Astuti, Novika Candra (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 12 Nomor 1 Tahun 2018DO - 10.24843/MATRIK:JMBK.2018.v12.i01.p05, 2018)
Little Bandung is a concept to help Bandung creative SMEs to enter foreign market. This study aims to understand obstacles, motivation, expectation and strategies in preparing Bandung SMEs in international environment. This research used qualitative and quantitative method to collect data by interviewing and conducting focus group discussion toward 15 respondents (owner/manager) from SMEs in creative industries listed in the Book of Bandung creative products as well as spreading questionnaires to obtain deeper understanding. The results show that more than 90% respondents have previous experience in foreign market such as in Singapore and Malaysia. The major reasons to enter foreign market are to fill customers’ orders and develop business. The main barriers that SMEs are concerned with are laws and regulation and perception of no market abroad. This study suggests that Bandung government should create a website as a platform that connect with each of SMEs’ website and conduct market research to analyze Korean market. In addition the clarity of concept of Little Bandung and business management in Korea are needed to prepare it well before penetrating abroad.